2019
DOI: 10.1111/jipb.12813
|View full text |Cite
|
Sign up to set email alerts
|

Cryptochrome‐mediated hypocotyl phototropism was regulated antagonistically by gibberellic acid and sucrose in Arabidopsis

Abstract: Both phototropins (phot1 and phot2) and cryptochromes (cry1 and cry2) were proven as the Arabidopsis thaliana blue light receptors. Phototropins predominately function in photomovement, and cryptochromes play a role in photomorphogenesis. Although cryptochromes have been proposed to serve as positive modulators of phototropic responses, the underlying mechanism remains unknown. Here, we report that depleting sucrose from the medium or adding gibberellic acids (GAs) can partially restore the defects in phototro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…Previously, the expression of PHOT2 in mature leaves was shown to be significantly induced by high light irradiation (Labuz et al, 2012 ). We also found that RPT2 expression significantly increased with increasing BL intensity (Zhao et al, 2020 ). Both KAC1 and PMI2 have been shown to be important for the regulation of chloroplast movement, although the underlying mechanisms of their functions are still unclear (Luesse et al, 2006 ; Suetsugu et al, 2010 ).…”
Section: Discussionmentioning
confidence: 66%
“…Previously, the expression of PHOT2 in mature leaves was shown to be significantly induced by high light irradiation (Labuz et al, 2012 ). We also found that RPT2 expression significantly increased with increasing BL intensity (Zhao et al, 2020 ). Both KAC1 and PMI2 have been shown to be important for the regulation of chloroplast movement, although the underlying mechanisms of their functions are still unclear (Luesse et al, 2006 ; Suetsugu et al, 2010 ).…”
Section: Discussionmentioning
confidence: 66%
“…In a nonmutually exclusive alternative, redundant pathways for hypocotyl phototropism have been suggested in Arabidopsis (45), in which AtCDKA;1 may participate. Further studies on AtCDKA;1 function in Arabidopsis will extend our understanding of the mechanisms underlying light responses in land plants.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of phytochromes and the blue light photoreceptors cryptochromes in the nucleus regulates the expression of several genes that indirectly contribute to modulate phototropic responses (reviewed by Goyal, Szarzynska, & Fankhauser, 2013; Liscum et al, 2014). In this context, several studies indicate that cryptochromes positively regulate the blue‐light mediated phototropism in etiolated seedlings (Kang, Lian, Wang, Huang, & Yang, 2009; Nagashima et al, 2008; Ohgishi, Saji, Okada, & Sakai, 2004; Tsuchida‐Mayama et al, 2010; Zhao et al, 2019). Moreover, the behaviour of phyA cry1 cry2 loss‐of‐function mutants suggests that both phyA and cryptochromes are required, to some extent, for the phototropic response (Tsuchida‐Mayama et al, 2010).…”
Section: Introductionmentioning
confidence: 99%